Healthcare recommendations for Joubert syndrome. Issue 1 (11th November 2019) - Bachmann‐Gagescu, Ruxandra; Dempsey, Jennifer C.; Bulgheroni, Sara; Chen, Maida L.; D'Arrigo, Stefano; Glass, Ian A.; Heller, Theo; Héon, Elise; Hildebrandt, Friedhelm; Joshi, Nirmal; Knutzen, Dana; Kroes, Hester Y.; et al.
Abstract: Joubert syndrome (JS) is a recessive neurodevelopmental disorder defined by a characteristic cerebellar and brainstem malformation recognizable on axial brain magnetic resonance imaging as the "Molar Tooth Sign". Although defined by the neurological features, JS is associated with clinical features affecting many other organ systems, particularly progressive involvement of the retina, kidney, and liver. JS is a rare condition; therefore, many affected individuals may not have easy access to subspecialty providers familiar with JS (e.g., geneticists, neurologists, developmental pediatricians, ophthalmologists, nephrologists, hepatologists, psychiatrists, therapists, and educators). Expert recommendations can enable practitioners of all types to provide quality care to individuals with JS and know when to refer for subspecialty care. This need will only increase as precision treatments targeting specific genetic causes of JS emerge. The goal of these recommendations is to provide a resource for general practitioners, subspecialists, and families to maximize the health of individuals with JS throughout the lifespan.